Diseño e implementación de un multiplicador de fuerzas para la optimización de energía eléctrica, para el cuarto de máquinas de energías alternativas de la carrera de ingeniería electromecánica de la Universidad Técnica Cotopaxi, periodo 2016 - Taipe Mora, Néstor Daniel (2016)
The energy storage devices afford to improve the quality and security of electricity supply. This paper is based on a whirling mass device, called flywheel which is connected to an electrical machine in order to transform electrical energy into rotational kinetic energy and vice versa. As the main objective is presented to deploy a force multiplier for optimization the electricity generation process at Electromechanical Engineering Career Laboratory in the Technical University of Cotopaxi. To achieve the objective, this research is divided into two parts; in the first part, the design and implementation of the system where its behavior to different initial conditions and perturbations is analyzed, showing that the storage system flywheel energy has a quick, accurate and robust response; in the second part, the graphical visualization by LabVIEW software using voltage and current behavior in electricity generation is detailed.